2019
DOI: 10.1016/j.spinee.2018.08.016
|View full text |Cite
|
Sign up to set email alerts
|

Highlighting discrepancies in walking prediction accuracy for patients with traumatic spinal cord injury: an evaluation of validated prediction models using a Canadian Multicenter Spinal Cord Injury Registry

Abstract: Previously tested prediction models demonstrated a lower predictive accuracy for AIS B+C than AIS A+D patients. These models were unable to effectively prognosticate AIS A+D patients separately; a failure that was masked when amalgamating the two patient populations. This suggests that former prediction models achieved strong prognostic accuracy by combining AIS classifications coupled with a disproportionately high proportion of AIS A+D patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
10
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(10 citation statements)
references
References 28 publications
0
10
0
Order By: Relevance
“…This model was simplified having only the three remaining variables: age (<65 years vs ≥65 years), L3 motor score, and S1 light touch score [ 13 ]. Critical analysis of both models with different patient cohorts revealed that these models achieved high prognostic accuracy for combined AIS categories, whereas applying these models to single AIS sub-groups led to considerably lower accuracy, thus limiting their applicability [ 14 •, 15 ]. Models that include additional parameters or use machine learning algorithms have been developed but showed comparable or inferior predictive accuracy of patient’s mobility [ 16 19 ].…”
Section: Clinical Outcome Measuresmentioning
confidence: 99%
“…This model was simplified having only the three remaining variables: age (<65 years vs ≥65 years), L3 motor score, and S1 light touch score [ 13 ]. Critical analysis of both models with different patient cohorts revealed that these models achieved high prognostic accuracy for combined AIS categories, whereas applying these models to single AIS sub-groups led to considerably lower accuracy, thus limiting their applicability [ 14 •, 15 ]. Models that include additional parameters or use machine learning algorithms have been developed but showed comparable or inferior predictive accuracy of patient’s mobility [ 16 19 ].…”
Section: Clinical Outcome Measuresmentioning
confidence: 99%
“…The clinical prediction rules for predicting walking after SCI have limitations. These tools are not as accurate in predicting walking for those with more severe, but incomplete SCIs (AIS B and C) where prediction would be most clinically useful [6]. Early after SCI, sensorimotor testing for proper AIS classification may not be possible to perform-in instances of sedation, polytrauma, and/or concomitant brain injury-thus, the clinical prediction rules would not be available or applicable.…”
Section: Introductionmentioning
confidence: 99%
“…In rehabilitation research, the role of functioning as key health indicator complementing mortality and morbidity [12] poses the question of how prediction research, and specifically prediction models, can improve the use of functioning information for practice. In SCI literature, various efforts have been undertaken to develop and/or validate prediction models for outcomes related to specific aspects of functioning, such as ambulation, [13][14][15][16][17][18][19][20] or bladder and bowel outcomes [21][22][23] . Predictor finding studies for several functioning outcomes have already been reviewed and synthesized [24][25][26][27] .…”
Section: Introductionmentioning
confidence: 99%